2015
DOI: 10.1007/s12040-014-0534-9
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and its role in forecasting energy demand in buildings: A case study of Douala City, Cameroon

Abstract: The foremost role of a building is to assure the comfort of its occupants. The thermal comfort of a building depends on the outdoor climate and requires a demand in energy for heating and cooling. In this paper, demand of energy (heating/cooling) in the buildings is discussed in Douala, Cameroon. Daily data of the last 40 years coming from five weather stations of Cameroon have been studied. Some forecasts have been carried out with 14 GCM models, associated to three future climate scenarios B1, A2, and A1B. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 17 publications
4
2
0
Order By: Relevance
“…From this table, it was observed that renovation allows reducing the energy consumption between 9.7% and 35.5% in these three cities. Furthermore, the energy demand is 63% higher in the coastal region than in high altitude regions, which confirms the previous study carried out by Nematchoua et al [29][30][31][32]. In particular, in Table 7, it can be observed that, after the revision process, the zero-energy objective is respected (the sum of the energy demand and the green energy generated by some photovoltaic panels (PV) is equal to zero).…”
Section: Case Of Residence Building Located In the Tropical Regionsupporting
confidence: 86%
“…From this table, it was observed that renovation allows reducing the energy consumption between 9.7% and 35.5% in these three cities. Furthermore, the energy demand is 63% higher in the coastal region than in high altitude regions, which confirms the previous study carried out by Nematchoua et al [29][30][31][32]. In particular, in Table 7, it can be observed that, after the revision process, the zero-energy objective is respected (the sum of the energy demand and the green energy generated by some photovoltaic panels (PV) is equal to zero).…”
Section: Case Of Residence Building Located In the Tropical Regionsupporting
confidence: 86%
“…In this table, we can see that the passive strategy allows the improvement in indoor air (relative humidity and air temperature) between 10% and 25%, according to the cities and seasons. These results support the conclusions of several researchers who demonstrated that the application of passive strategy techniques can have a significant effect on the indoor climate [33,34]. Between 2017 and 2050, it is predicted that the indoor temperature will increase up to 1 • C, while the relative humidity will tend to decrease up to 5%.…”
supporting
confidence: 89%
“…The different temperature variations in the different cities are shown in Table 5. This variation is almost identical to that observed in several countries in the Sub-Saharan Africa [46] .…”
Section: Case Of Variation In the Annual Maximum Temperaturesupporting
confidence: 88%